Glycated hemoglobin HbA1c, waist circumference, and waist-to-height ratio in overweight and obese adolescents - Elysa Nur Safrida; Neti Nurani; Madarina Julia (Indonesian Pediatric Society, 2017)
Background Central obesity has been associated with a high risk of insulin resistance. Waist circumference and waist-to-height ratio are anthropometric indices for determining central obesity and have been associated with increased blood pressure, cholesterol, and insulin levels. In adults, fat distribution around the waist is a valid predictor of glycated hemoglobin (HbA1c)levels, and is currently recommended by experts as a diagnostic tool for diabetes. Central obesity measurement has advantages over fasting blood glucose and oral glucose tolerance tests, as it is simple and inexpensive to perform.Objective To assess for correlations between HbA1c level and waist circumference as well as waist-to-height ratio and to assess factors potentially associated with HbA1c levels in overweight and obese adolescents.Methods This cross-sectional study was done in four junior high schools in Yogyakarta, which were obtained by cluster sampling. Overweight and obese students who were generally healthy were included in the study. Subjects underwent waist circumference and waist-to-height ratio measurements, as well as blood tests for HbA1clevels.Results Sixty-seven children participated in the study, with 48 girls (71.6%) and 19 boys (28.4%). Waist circumference and HbA1c levels were not significantly associated (r=0.178; P=0.15). However, waist-to-height ratio and HbA1c levels had a weak positive correlation (r=0.21; P=0.04). Linear regression analysis revealed that waist-to-height ratio had a significant association with HbA1c level (P=0.02), but age, sex, and nutritional status did not.Conclusion Waist-to-height ratio is correlated with HbA1c levels in overweight and obese adolescents.